Effect of Sulfur-Containing Compounds on Growth of Methanosarcina barkeri in Defined Medium - Mazumder, Tapan K. (1986)
Methanosarcina barkeri Fusaro (DSM 804) could grow on methanol in a mineral medium containing cysteine or thiosulfate as the sole sulfur source. Optimum growth occurred at cysteine concentrations of 1 to 2.8 mM and at thiosulfate concentrations of 2.5 to 5 mM. No inhibition of growth was observed even when these concentrations were doubled in the culture medium. Under the optimum cysteine and thiosulfate concentrations, the generation times of the organism were about 8 to 10 and 10 to 12 h, respectively, giving a cell yield of about 0.14 to 0.17 and 0.08 to 0.11 g (dry weight)/g of methanol consumed. The organism metabolized cysteine and thiosulfate during growth, giving rise to sulfide in the culture medium. H(2)S evolution from cysteine and thiosulfate was catalyzed by two enzymes, namely cysteine desulfhydrase and thiosulfate reductase, respectively, as revealed by enzyme assay in the crude cell-free extract of the organism.